Evaluasi strategi UPTD SPAM dalam pengelolaan air bersih di Kelurahan Bahontula: Pendekatan teori strategi sektor publik - Fahmi Surya Abdi; Muallim Muallim; Asmansyah Asmansyah; Edhib Harits Anugrah; Andi Nuzul Akbar (Nur Science Institute, 2026)
Prolonged clean water crises caused by the clash between public service infrastructure and mining activities pose severe challenges to local government governance. In Bahontula Village, North Morowali Regency, this situation led to a five-month paralysis of water distribution (April–August 2024) due to damage to the main water pipe. Addressing this issue, this study aims to analyze the strategic effectiveness of the Regional Technical Service Unit (UPTD) of the Drinking Water Supply System (SPAM) using a qualitative descriptive approach. Based on Geoff Mulgan's strategic framework comprising Purposes, Environment, Direction, and Action, data were collected through interviews, observation, and documentation. The findings indicate that while the UPTD had clear Purposes and executed Action through technical repairs, the strategy was persistently hindered in the Environment dimension by budget constraints and the destructive impact of mining operations. Furthermore, although Direction was implemented via socialization, community satisfaction remained low due to fluctuating water flow and turbidity during high rainfall. In conclusion, the UPTD's water management strategy is not yet fully effective, as it is heavily constrained by external factors, underscoring the urgent need for stronger environmental regulations and stricter inter-institutional coordination in the industrial sector.